Hydropower and the geopolitics of renewable energies in the Amazon Basin - Castro,Carlos Potiara (2021)
Abstract This article aims to reflect on the strategic importance of hydroelectric energy generated in the Amazon region for the interconnected Brazilian system. Its quantification shows a regional potential for higher energy generation compared to the current production of pre-salt oil. We consider this issue from the perspective of the geopolitics of renewable energy that brings new and relevant elements. In this article, the analytical framework focuses on path-dependence, smart-grids and energy-intensive societies and their energy security policies. As a result, we observe that in the current configuration, the advent of renewable energies can be an additional element of a long-term economic specialization of the Amazon, with worrying consequences from a socio-environmental perspective.